Complementary Therapy In Overcoming Depression Schizophrenia Patients - I Wayan Septa Wijaya; I Gede Putu Oka; Satriya Pranata; Fatkhul Mubin (Journal Nursing Research Publication Media (NURSEPEDIA), 2026)
Background: Schizophrenia is a mental health condition that places a significant burden on those affected. It typically emerges during adolescence or early adulthood and is often marked by recurrent positive symptoms. When depressive symptoms are present in individuals with schizophrenia, these individuals often struggle to fulfill their roles within their families and society effectively. Treatment options include both pharmacological and non-pharmacological strategies. Non-pharmacological interventions can be delivered through complementary therapies. Aims: This literature review aims to identify such therapies that can help alleviate depression in patients with schizophrenia. Method: In the process article search via PubMed and Science Direct using the keyword "Depression and schizophrenia and complementary therapy” found of 797 article, PubMed 407 and Science Direct 390. 197 duplicate articles were removed, leaving 600 articles. The next step was filtering, filtering the titles and abstracts of 600 articles, resulting in 556 irrelevant articles, leaving 44 articles was in accordance with of the 44 artcles was in accordance with the inclusion an exclusion criteria, and 40 articles were not in accordance with the topic, so 4 articles were reviewed. Result: The analysis of selected studies indicates that these complementary therapies play a crucial role in non-drug management approaches and have demonstrated effectiveness in reducing depressive symptoms among patients with schizophrenia. Conclusion: It can be concluded that the provision of complementary therapy has proven effective in treating depression in pattients with schizophrenia.